A modelling approach and a case study to answer the question: What does it take to retrofit a community to net-zero energy?. (August 2021) - Wills, Adam D.; Beausoleil-Morrison, Ian; Ugursal, V. Ismet
Abstract: In order to have an immediate impact on building energy-related emissions, existing buildings need to be addressed. To inform policy and technical decisions, detailed mathematical models are required which can explore numerous building retrofit solutions and their energy and emissions performance. This paper describes the adaptation of a hybrid statistical and engineering-based model for residential building stock in Canada to analyze community-scale energy retrofits. The modelling domain includes both envelope and mechanical retrofits, as well as district renewable energy systems. This model is then applied to a case study of converting a community of fifty 1980's vintage single-detached homes to achieve net-zero energy. The case study demonstrated that deep envelope retrofits and fuel switching from natural gas to electric heat pump systems reduce community energy demand by 69%. Saturating available roof area with photovoltaics was able to achieve net-zero balance. By considering net-zero at the community-scale, individual buildings that did not achieve net-zero were offset by net-exporting neighbours. Annual community emissions of the retrofit reduced emissions by 95%. The analysis also highlights the significant impact on electrical infrastructure due to solar generation and energy demand mismatch. Highlights: Developed building stock model to assess community energy retrofits of existing homes. Deep envelope retrofits and fuel switching reduced energy demand by 69%. Net-negative buildings are offset by net positive within the community. Net-zero community reduced annual emissions by 95%. PV system has significant impacts on electrical grid when no storage available.